EBIB - The Electronic Library, the electronic platform of the Polish Librarians Association - Sójkowska, Iwona; Podgórski, Filip; Rożniakowska, Małgorzata (Dominican University Graduate School of Library and Information Science, River Forest, Illinois, USA, 2006)
EBIB — the “Electronic Library” (in Polish: Elektroniczna BIBlioteka at http://www.ebib.info/)refers to both the journal and the only professional electronic information platform for librariansin Poland. The platform was launched and is maintained by the group of active librarians from several libraries in Poland.